Antenatal diagnosis of idiopathic dilatation of pulmonary artery with 3D power doppler imaging. Issue 2 (20th May 2016) - Yang, Pei‐Yin; Sajapala, Suraphan; Yamamoto, Kenta; Mori, Nobuhiro; Kanenishi, Kenji; Koyano, Kosuke; Kusaka, Takashi; Hata, Toshiyuki
ABSTRACT: We present a case of antenatal diagnosis of idiopathic dilatation of the pulmonary artery by three‐dimensional power Doppler imaging (HDliveFlow with silhouette mode). Two‐dimensional sonography clearly demonstrated a 10.4‐mm‐diameter fetal pulmonary artery (PA), whereas the aorta (Ao) diameter was 5.04 mm. HDliveFlow clearly demonstrated the spatial relationships and different sizes of PA and Ao. The PA size returned to normal (8.0 mm) on the 11th day after birth (Ao: 9.0 mm). HDliveFlow may be an adjunctive tool to two‐dimensional sonography to diagnose abnormalities of fetal great vessels. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :121–123, 2017;